2023
DOI: 10.1371/journal.pone.0293184
|View full text |Cite
|
Sign up to set email alerts
|

The impact of national income and vaccine hesitancy on country-level COVID-19 vaccine uptake

Javad Moradpour,
Ali Shajarizadeh,
Jasmine Carter
et al.

Abstract: Background The rapid development and rollout of COVID-19 vaccines helped reduce the pandemic’s mortality burden. The vaccine rollout, however, has been uneven; it is well known that vaccination rates tend to be lower in lower income countries. Vaccine uptake, however, ultimately depends on the willingness of individuals to get vaccinated. If vaccine confidence is low, then uptake will be low, regardless of country income level. We investigated the impact on country-level COVID-19 vaccination rates of both nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Several studies have looked at the impact of GDP on COVID-19 vaccination uptake [ 180 , 181 , 182 , 183 ] but none have looked at the impact of GDP on vaccine acceptance or hesitancy. Here we present the first study, to the best of our knowledge, that showed that WB income level was associated with VA and VH, but that percentage GDP spent on vaccine procurement was not associated with VA and VH.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have looked at the impact of GDP on COVID-19 vaccination uptake [ 180 , 181 , 182 , 183 ] but none have looked at the impact of GDP on vaccine acceptance or hesitancy. Here we present the first study, to the best of our knowledge, that showed that WB income level was associated with VA and VH, but that percentage GDP spent on vaccine procurement was not associated with VA and VH.…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to greater heterogeneity in decisions about childhood vaccinations, which in turn may affect the level of hesitancy among parents. However, the presence of these factors, in varying proportions, may be individual for each country or society [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%